Effects of accession, spacing and pruning management on in-situ leaf litter decomposition of Jatropha curcas L. in Zambia. (October 2015) - Negussie, Aklilu; Degerickx, Jeroen; Norgrove, Lindsey; Achten, Wouter M.J.; Hadgu, Kiros Meles; Aynekulu, Ermias; Muys, Bart
Abstract: Jatropha curcas L. leaf litter decomposition and subsequent nutrient release was monitored in three experimental J. curcas plantations in Zambia, comparing accessions from six countries, pruned versus non-pruned and different plant spacings. Leaf litter production was low (267–536 kg ha −1 at the end of the growing season) and contained, on average, 1.23% N, 0.14% P and 2.61% K. Litter decomposed rapidly, losing 80% of total mass between 70 and 105 days after incubation in the field and followed a negative exponential pattern with an average decomposition constant, k, of 0.08 week −1 . No significant effects of plant accession, plant spacing or pruning on the decomposition rate were detected. K, P, Mg and Na had nutrient release rates exceeding mass loss, explained by their high mobility and solubility, together with high soil temperature and rainfall conditions. Others, such as Ca and Mn, were initially retained in the decaying leaf litter before later release. The rate of N release closely approached that of mass loss. J. curcas litter can be a supplemental source of nutrients in areas known for nutrient deficiency and low organic matter, which represents an additional input in intercropping systems above biofuel production. Considering that the total primary nutrient input through J. curcas litterfall to the soil is limited (for example, for nitrogen between 9.7 and 14.2 g kg −1 and for phosphorus between 0.8 and 1.9 g kg −1 ), organic or mineral fertilizer application remains crucial to satisfy fully the nutrient requirements of surrounding crops. Highlights: Jatropha curcas leaf litter production was low (267–536 kg ha −1 ). Total nutrient input through J. curcas litterfall to the soil is limited. J. curcas litter decomposed rapidly, losing 80% of its total mass after 70 days. J. curcas leaf litter decomposition showed a negative exponential pattern (average decomposition constant k = 0.08 week −1 ).